Combination of D0 measurements of the top quark mass - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2017)
We present a combination of measurements of the top quark mass by the D0 experiment in the lepton+jets and dilepton channels. We use all the data collected in Run I (1992-1996) at s=1.8 TeV and Run II (2001-2011) at s=1.96 TeV of the Tevatron pp collider, corresponding to integrated luminosities of 0.1 fb-1 and 9.7 fb-1, respectively. The combined result is: mt=174.95±0.40(stat)±0.64(syst) GeV=174.95±0.75 GeV.